ANALISIS PENGARUH JUMLAH PRODUKSI, KURS DOLLAR AMERIKA SERIKAT, DAN INFLASI TERHADAP VOLUME EKSPOR TEH INDONESIA TAHUN 2010-2018 - Widiartha, I Gusti Agung Bagus Krishna; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 1 (2021): VOL 10 NO 1, JANUARI 2021 [ 1 - 450 ], 2021)
Indonesia is rank 7 th as the world’s largest tea producer and exporter Based on the results of the analysis found that the amount of production, the US dollar exchange rate, and inflation simultaneously influence the export volume in Indonesia. The amount of production partially has a positive and not significant effect on the volume of tea exports in Indonesia, the US Dollar exchange rate has a partially negative effect on the volume of tea exports in Indonesia, and inflation has a partially positive effect on the volume of tea exports in Indonesia. Inflation is a variable that has a dominant influence on the volume of tea exports in Indonesia. Increasing the amount of production must be balanced with an increase in the quality of tea products so as to increase tea exports in Indonesia. The weak Rupah exchange rate of the US Dollar is able to increase demand from the importer side because the price of domestic goods is cheap so that it can increase the volume of tea exports. The need for intervention from the government and central bank to regulate the level of inflation in the country to remain below 10 percent. Keywords : export volume, total production, US Dollar exchange rate and inflation.